Aesthetic Expression of Personified Characters in the Poems of Majeed Amjad - Sherreen, Bushra (sourcecoder, 2024)
This research paper is centered around the key concept of Personification. The literary device personification symbolizes the attribution of human qualities and sentiments to inanimate or non-living objects. This technique has been used in literature since ancient times. In the modern era, poets are compelled by contemporary requirements to use this technique in their poetry. One such poet is Majeed Amjad whose poetry represents twentieth century. Amjad personifies different aspects and objects of nature in his poems, the study of which is the central aim of this research paper. This paper first highlights the Western understanding of personification by quoting examples. Then it analyzes how different phenomena and objects are personified in Amjad's poetry including trees, grass, leaves, echo, a beggar woman, a blood spot, and many other. This paper brings together the Western and Oriental literary trends in Urdu which marks its vast scope and implies further research in this domain.